Performance Model of Planning Consulting Companies in Green Building and Sustainable Design Planning Achievements - Prianto, Kusnul; Antariksa; Wisnumurti; Sarwono (Jurnal Pembangunan dan Alam Lestari, 2024)
This study is a collaborative effort aimed at finding a performance model for a planning consulting firm for achieving green building and sustainable design planning. The method used in this research is qualitative, with SEM analysis tools to find an ideal model. The results of the study found the Planning Consulting Company's performance model in achieving sustainable and green building design planning. It was found that the first model patterned a positive relationship between the consulting company performance indicators and green building. Meanwhile, the second model shows a positive relationship between the Green Building Planning Consulting Company's performance indicators and sustainable development. The test results for the coefficient of determination (R-square) obtained from the first model are the influence of variables site management to wastewater management on the variable green building of 0.757 so that variable green building can be explained by variables site management to wastewater management of 75.7%. Other variables outside this study influence the remaining 24.3%. The coefficient of determination (R-square) obtained from the second model is the effect of the variables green building and site management to wastewater management on the variable sustainable development of 0.790, so the variable sustainable development can be explained by the variables green building and site management to wastewater management of 79%, and other variables outside of this study influence the remaining 21%. We invite you to be part of this collaborative effort and share your insights on these findings. Keywords: performance model, planning consultant, green building, sustainability